Planning of banana plant development based on the land conservation aspect in Jenawi District - Indri Hapsari Pusponegoro; M Mujiyo; S Suntoro; Aktavia Herawati; Hery Widijanto (Brawijaya University, 2018)
Banana is one type of fruits that is very potential to grow to support food security because it contains source of vitamins, minerals, and carbohydrates. Jenawi District has a dry land area that is potential for the development of banana plants. The purpose of this research was to plan the development of banana plants in accordance with the land conservation aspect against the threat of the erosion. The research was conducted by making land unit map, field survey, analysis of soil sample in the laboratory, and data analysis of erosion hazard level. Land unit mapping was made by overlay method so there were 12 units of land with the same land conditions. Field survey and sample analysis at the observation point was conducted to obtain the parameters: slope gradient, depth of solum, surface unity, slope length, bulk density, soil texture, soil c-organic, and soil permeability. The analysis of land conservation aspects for banana plants was determined from the level of erosion hazard with the USLE (Universal Soil Loss Equation) method. The results showed that the threat of moderate to severe erosion hazard for banana crops was overcome by the efforts of land conservation techniques using a good construction bench terrace. The threat of erosion hazard after land conservation directives is very low to low. The amount of the erosion prediction for banana plant planning in garden is 35.80 t/ha/yr (unit B unit), land use of dry fields is 29.82 t/ha/yr (land unit I), 31.54 t/ha/yr (land unit K), and 13.72 t/ha/yr (unit land L).